Influence of organizational culture & intellectual capital on business performance in textile industry of Pakistan - Fahim, Syed Muhammad (Array, 2021)
This paper aims to find out the extent to which organizational culture and intellectual capital influence the textile industry"s business performance in Pakistan. The study uses causal and explanatory research design. Several 200 textile industry employees participated in this survey, selected as the study sample using the purposive sampling technique. The study detects that both organizational and intellectual capital directly impact the textile firms" business performance. However, the impact of intellectual capital on business performance is more substantial than that of organizational culture. The mediating effect of technological innovation in the relationship between organizational culture and business performance is also supported. The study can be used by the textile industry managers to set up policies on how to improve business performance in the textile firms. The study also fills the literature gap as prior studies do not have worked on the mediating aspect of technological innovation.